BEAUTY AND HEALTH - Yusupova Sevinch Lutfullo qizi; Tilavov Davronbek Davlat o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: We know that almost all women want to be beautiful.Being beautiful in a natural way is the dram of all women.You can make masks from things you have at home.Applying various masks can cause spots on the face.That’s why you need to be careful.When it comes to health,it is important thing for a person.In this article,you will find some necessary information about beauty and helath,and you will learn useful information.